OPTIMIZATION OF MORINGA OLEIFERA LEAF TEA ADMINISTRATION FOR INCREASING HEMOGLOBIN (HB) LEVELS IN ANEMIC PATIENTS - Zahro, Saniah; Yulinda, Ratna; Sauqina (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
Anemia remains a significant nutritional challenge in Indonesia. One of the leading causes of anemia is iron deficiency, which is attributed to the requirement of essential micronutrients in hemoglobin synthesis. Various plant sources have been explored for their potential in alleviating anemia, and one such candidate is the Moringa plant. Moringa leaves, in particular, are known for their rich iron content, and they are often processed into tea to address hemoglobin deficiencies. The primary objective of this study was to determine the optimal dosage of Moringa leaf tea for increasing hemoglobin levels in anemic patients. We conducted quantitative research employing the true experimental method, with a completely randomized design (CRD) involving four distinct treatments and five repetitions. The results revealed the following hemoglobin levels in the treatment groups: treatment 1 (1 gram) resulted in a hemoglobin level of 4.08 g/dl, treatment 2 (1.5 grams) showed a level of 4.78 g/dl, and treatment 3 (2 grams) resulted in a level of 4.08 g/dl. Notably, the control group, which did not receive any treatment, did not exhibit any significant increase in hemoglobin levels. Applying the Bonferroni Post Hoc test to compare the control group with the treatment groups, we observed a p-value of 0.000, where the p-value was less than 0.05, signifying a significant difference in hemoglobin levels before and after treatment. The most effective dose of Moringa leaf tea, determined to be 1.5 grams, yielded the most substantial increase in hemoglobin level.